Platelet-Rich Plasma Ameliorates Monosodium Iodoacetate-Induced Ankle Osteoarthritis in the Rat Model via Suppression of Inflammation and Oxidative Stress. (19th January 2021) - Ragab, G. H.; Halfaya, F. M.; Ahmed, O. M.; Abou El-Kheir, W.; Mahdi, E. A.; Ali, T. M.; Almehmadi, M. M.; Hagag, U.
Abstract : Until now, there is no treatment that cause complete cure of the chronic inflammatory and degenerative disease, osteoarthritis (OA). Moreover, the underlying mechanisms of OA development and progress are not fully elucidated, and the present pharmacological treatment alternatives are restricted and associated with adverse side effects. Thus, the present study was conducted to evaluate the role of platelet-rich plasma (PRP) in the remedy of OA in the rat model in terms of inflammation, ankle histopathological alterations, and oxidative stress. OA was induced in male Wistar rats by injection of MIA (2 mg)/50 µ L isotonic saline in the right ankle joint for two successive days in each rat. After the 2 nd MIA injection, the osteoarthritic rats were allocated into two groups such as the MIA group (group 2) and MIA + PRP group (group 3). The MIA + PRP group was treated with PRP (50 µ L) by injection into the ankle joint of the right hind limb of each rat at days 14, 21, and 28 after the 2 nd injection of MIA. The same equivalent volume of saline, as a substitute of PRP, was injected into the ankle joint of each rat of the normal control group (group 1) and MIA group (group 2) at the same tested periods. Swelling of joint, bodyweight, total leucocytes count (TLC), and morphological as well as histological changes of ankle joints were evaluated. Serum lipid peroxides (LPO), glutathione (GSH), and glutathione S-transferase (GST) levels were examined as biomarkers of oxidative stress. Serum tumor necrosis factor- α (TNF- α ), interleukin-17 (IL-17), and interleukin-4 (IL-4) were investigated by ELISA as biomarkers of inflammation. In addition, magnetic resonance imaging (MRI) was carried out to investigate the soft tissues in joints. The obtained results revealed that PRP reduced LPO and increased GSH and GST levels in osteoarthritic rats. Also, PRP significantly diminished serum TNF- α and IL-17 levels, while it increased IL-4 serum levels in rats with MIA-induced OA. Morphological observations, histological analysis, and MRI revealed a gradual diminishing in joint inflammation and destruction of cartilage in PRP-injected osteoarthritic rats. Based on these results, it can be suggested that PRP has antiarthritic potential in MIA-induced OA, which may be mediated via suppression of inflammation and oxidative stress.